Phenolic Iron Complexes Protect Glacier Ice Algae (Zygnematophyceae) Against Excessive UV and VIS Irradiation - Procházková, Lenka; Mojzeš, Peter; Ráček, Jan; Nedbalová, Linda; Remias, Daniel (Environmental microbiology reports, 2025)
Melting glacier surfaces are increasingly affected by blooms of psychrophilic microalgae, which darken the ice and lower its albedo, accelerating melting. These microalgae contain distinct vacuoles filled with brownish pigments that were earlier described as the unusual plant phenol purpurogallin. Recently, we discovered so far unreported, large amounts of iron dissolved in aqueous extracts of the glacier ice algae Ancylonema alaskanum. Since the vacuole content was very dark but the chromatographically isolated, aforementioned phenol was only yellowish, a putative complexation of iron with purpurogallin was assumed to be the reason. Application of several protocols, including Raman microscopy on both living cells and extracts, provided strong evidence that this microalga sequesters iron and forms organic metal complexes. Consequently, substantial amounts of so far uncharacterised Fe-complexes of purpurogallin are inferred to be present in Ancylonema, and that putative polymerisation of this compound impeded an earlier analytical discovery. This finding holds significant ecological implications for cold regions. The pigmentation not only enhances the tolerance of glacier ice algae to excessive UV and visible radiation but also influences our current understanding of the biochemical iron cycle in cryosphere-dominated polar and alpine regions. Further downstream consequences of this biological iron source remain to be elucidated.
Keywords: železo; Microalgae; Ultraviolet Rays; světlo; ultrafialové záření; ledový příkrov; cryoflora; glaciers; Ice Cover; Phenols; Raman microscopy; Light; polyphenols; mikrořasy; Iron; fenoly; secondary pigmentation